Investigating the effects of single-dose intranasal testosterone on economic preferences in a large randomized trial of men - Anna Dreber; Magnus Johannesson; Gideon Nave; Coren L. Apicella; Shawn N. Geniole; Taisuke Imai; Erik L. Knight; Dylan Manfredi; Pranjal H. Mehta; Valentina Proietti; Steven J. Stanton; Alina Zeltikova; et al. (Proceedings of the National Academy of Sciences, 2025)
There is conflicting evidence on whether testosterone affects economic preferences such as risk taking, fairness, and altruism, with most evidence coming from correlational studies or small testosterone administration studies. To credibly test this hypothesis, we conducted a large-scale, preregistered, double-blind randomized controlled trial with 1,000 male participants—10 to 20 times larger than typical prior studies. Participants were randomly allocated to receive a single dose of either placebo or intranasal testosterone, and carried out a series of economic tasks capturing social preferences, competitiveness, and risk preferences. We find no evidence of a treatment effect for any of our nine primary outcome measures, and no strong evidence of an association between basal salivary testosterone and economic preferences within men. These results fail to conceptually replicate previous high-impact publications reporting positive findings in smaller samples, calling into question the idea that short-term testosterone fluctuations are important drivers of men’s economic preferences. Our results do not rule out the possibility that different effects might emerge under alternative dosages, administration protocols, or task timings, or that behavioral effects differ between men and women. The potential for developmental or long-term effects of testosterone also remains an open question for future research, though such effects are ethically challenging to investigate experimentally in humans.